READING, ENCODING, ANNOTATING, AND PONDERING (REAP): THE STRATEGY TO IMPROVE FOURTH SEMESTER STUDENTS’ COMPREHENSION IN READING - Erniyati, Yelni (Universitas Muhammadiyah Palembang, 2024)
This study aims to describe the process of teaching and learning reading comprehension and improve students' reading comprehension ability by applying the REAP strategy. The researcher used classroom action research at the class A of the fourth semester students of English department of IAIN Kerinci. The class consisted of 22 students. The researcher conducted this study in two cycles and three meetings per cycle. Observation and test were employed in obtaining the data. For the test, the researcher used a reading comprehension test. The results showed that the process of teaching reading using the REAP strategy is very interesting. Students showed their participation during class. The results also showed an improvement in students' reading comprehension. This can be considered from the student's scores. It can be summarized that the REAP strategy could be used as a strategy for teaching reading comprehension.